Ekspresi Pengalaman Agama Budayawan Sunda Yat R Dalam Serial Dongeng Si Rawing Pada Chanel Youtube Radio Cakra Bandung - Hermawan, Ucep; Darmawan, Dadang; Qomaruzzaman, Bambang (Indonesian Journal of Religion and Society, 2024)
The phenomenon of religious communication through online media, such as YouTube, has introduced a new mode of religiosity. This mode can be categorized into two types: religion online and online religion. Religion online involves using online media as a tool for disseminating religious messages and storing religious information, such as digital manuscripts and sermons, accessible anytime. Online religion, however, transcends this by making online media a space for religious communication and activities, as seen during the COVID-19 pandemic when religious practices moved online. This study focuses on the online religion aspect, examining the spiritual experiences expressed by Sundanese cultural figure Kang Yat R through the Si Rawing story series on YouTube. Using a qualitative case study approach, data was collected through in-depth interviews with Kang Yat R and analysis of YouTube content. The findings reveal that Si Rawing reflects Kang Yat R’s religious experiences in three forms: thought (doctrine), action (ritual), and community (group), aligning with Joachim Wach's perspective. This research highlights the importance of online platforms in preserving and conveying religious and cultural heritage to younger generations.